2017
DOI: 10.1002/fsn3.454
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evaluation of selected formulated milk barberry drinks using the fuzzy approach

Abstract: Amid rigid competition in marketing to accomplish customers' needs, the cost of disappointment is too high. In an effort to escape market disappointment, one of the options to be considered is probing for customer satisfaction through sensory evaluation. This study aims to rank the six selected milk-barberry drink formulae out of 24 (code numbers S3, S4, S15, S16, S17 and S18) each having different milk:barberry:pectin amount (7: 3: 0.2; 6: 4: 0.2; 7: 3: 0.4, 6: 4: 0.4, 5: 5: 0.4 and 6: 4: 0.4), respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
2
14
0
1
Order By: Relevance
“…The shelf life of fish, like other foods, highly related to consumer sensory acceptability 29,30 . The results of the sensory score of rainbow trout fillet samples are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The shelf life of fish, like other foods, highly related to consumer sensory acceptability 29,30 . The results of the sensory score of rainbow trout fillet samples are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sensory quality of foods can be evaluated based on total impression made on the mind of the consumers (Tahsiri, Niakousari, Khoshnoudi‐Nia, & Hosseini, ). The mean of sensory scores for various properties are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…2A). Earlier, Sant'Anna et al (2014) and Tahsiri et al (2017) showed that the incorporation of powders into formulations prompt a higher level of acidity during fermentation. On the one hand, this is due to the chemical composition of jumbo squid powder, and on the other hand, the production rates of lactic acid are increased as a result of the fermentation of more carbohydrates in the enriched medium by the lactic starter culture (Ale et al, 2016).…”
Section: Properties Of Fermenting Milkmentioning
confidence: 98%
“…Despite the higher viscosity and lower syneresis of yogurts produced with higher concentrations of jumbo squid powder (YM7, YM10), in terms of organoleptic properties such yogurts were not as sensory qualified as those produced with lower doses of powder (YM1, YM3). While sensory measurements are still subjective, the experience of the panelists has been known to correlate positively with food preference (Lopez-Enriquez et al, 2015;Tahsiri et al, 2017).…”
Section: Sensory Analysis Of Yogurtmentioning
confidence: 99%
See 1 more Smart Citation